Proceedings of the Fifth International Conference on Internet Multimedia Computing and Service 2013
DOI: 10.1145/2499788.2499827
|View full text |Cite
|
Sign up to set email alerts
|

Social circle analysis on ego-network based on context frequent pattern mining

Abstract: Effective organization and management of a user's ego-network is one of the effective means to deal with information overload. Manual organization methods are often time-consuming and difficult to promote. In this paper, an automatic identification of social circles model is proposed, which takes three factors into account: user's profile, relationship information, and interactive context information. Using closed frequent itemsets mining on users' interactive context, a user in egonetwork can belong to more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…One fundamental assumption of the model is that circles will be made up of close knit group friends who also share common properties or traits, but disregards the interactive contextual information of users. Xu et al, further studied the problem and consider not only the impact of individual attributes, but also care about the influence of interaction between individuals during circle formation. The similar problem is also studied by MacLean et al, but in the context of Email.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…One fundamental assumption of the model is that circles will be made up of close knit group friends who also share common properties or traits, but disregards the interactive contextual information of users. Xu et al, further studied the problem and consider not only the impact of individual attributes, but also care about the influence of interaction between individuals during circle formation. The similar problem is also studied by MacLean et al, but in the context of Email.…”
Section: Related Workmentioning
confidence: 99%
“…A number of participants in a survey reported that they were unaware of such functionality exists, or found it cumbersome or confusing to configure lists or customize privacy settings based on these lists . Thus, finding automated means of creating circles to provide semantically meaningful grouping of connections is now becoming a challenging area . It also provides researchers a rich and unprecedented opportunity to the analysis and model relationships among various objects in social networks with the aim of understanding how the behavior of individuals and their interactions translates into large‐scale social phenomenon .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations